Development of Local Food Processing for Stunting Prevention in the Early Life of Toddlers in Karanganyar Village, Kawalu District, Tasikmalaya City, Indonesia - Yana Listyawardhani; Januar Arifin Ruslan; Enok Sumarsih; Unang Unang (PT FORMOSA CENDEKIA GLOBAL, 2023)
In Indonesia, stunting continues to be a significant nutritional issue, particularly for young children. Failure to give children the nourishment they need during their crucial early growth and development stages is one of the causes. The activity aims to help mothers and cadres create local food processing to meet their nutritional needs and stop and lessen stunting. Community service occurs in Karanganyar Village, Kawalu District, Tasikmalaya City. The distribution of questionnaires to gauge the level of community knowledge before and following the exercise is one of the activities, along with counseling and training on regional food processing. Following this practice, the posyandu cadres' expertise and abilities changed, making them more equipped to prepare tasty and nutrient-dense snacks from local food sources.